Bovine abortion caused by Coxiella burnetii: report of a cluster of cases in Uruguay and review of the literature. (July 2019) - Macías-Rioseco, Melissa; Riet-Correa, Franklin; Miller, Myrna M.; Sondgeroth, Kerry; Fraga, Martin; Silveira, Caroline; Uzal, Francisco A.; Giannitti, Federico
A cluster of 4 bovine abortions caused by Coxiella burnetii occurred in a dairy herd in Uruguay during a 2-mo period. Case 1 consisted of a placenta from an aborted cow; cases 2–4 were fetuses and their placentas. Grossly, the placenta from one aborted cow had moderate, diffuse reddening of the cotyledons and loss of translucency of the intercotyledonary areas. No gross lesions were observed in the other 3 placentas. Microscopically, 2 of 4 placentas had fibrinonecrotizing placentitis with abundant intratrophoblastic gram-negative coccobacilli. C. burnetii was identified intralesionally by immunohistochemistry (IHC) in all 4 placentas, and by PCR and DNA sequencing in 3 placentas analyzed by these techniques. One fetus had mild neutrophilic alveolitis with multinucleate syncytial cells; no gross or microscopic lesions were observed in the other 2 fetuses examined. The lungs of the 3 fetuses were negative for C. burnetii by IHC. Tests performed to investigate other possible causes of abortions in the 4 cases were negative. C. burnetii causes Q fever in humans and coxiellosis in animals. Clusters of abortions in cattle by C. burnetii have not been reported previously, to our knowledge; this bacterium has been considered an opportunistic pathogen associated only with sporadic abortion in cattle. We present herein a cluster of 4 bovine abortions caused by C. burnetii in a dairy farm during a period of 2 mo and a review of the literature on C. burnetii infection in cattle.